Dynamic Study on Vanadium Extraction Process in Basic Oxygen Furnance: Modeling Based on Gibbs’ Free Energy Minimization - Zhenyu Zhou; Cong Luo (Metals, 2022)
Vanadium extraction process demands low residual vanadium and carbon loss, and variations of dissolved elements in hot metal must be determined to achieve it. A three parts dynamic model that applies the concept of Gibbs’ free energy minimization at the slag–metal interface is proposed. Modeling simulation results shows good uniformity with plant experimental data, and the presented model can describe the vanadium extraction process in BOF qualitatively well. The effects of coolant addition and oxygen flow rate have been studied by modeling. The lack of coolant will reduce (FeO) content and elevate the molten bath temperature, which are harmful to deep vanadium removal with less carbon loss in semi-steel. The excessive oxygen flow rate has little effect on residual [V], and there is more carbon loss because of higher (FeO) content and molten bath temperature.